Defamiliarization and science fiction: a schrodingerian approach to the construction of the literary object - Murr, Caroline Elisa (2022)
This paper aims at a description of the construction of literary objects in human experience, based on Erwin Schrödinger’s ideas about the construction of reality, published in his philosophical works from 1928 to 1964. It is suggested that the construction of such objects may be described through a process similar to the invariants’ retrieve and the construction of scientific objects, in a Schrödingerian approach. Nevertheless, such approach is not enough to explain some particular cases. Hence, it is needed to add the notion of defamiliarization, advanced by Viktor Shklovsky in 1917 and revisited by Sally Banes in 2003. This conception consists basically in making familiar things strange, instigating attention in its direction, in a memorable experience. Defamiliarization seems adequate to describe the moments in which expectations are broken and, sometimes, a return to sensations is observed. This article also explores some examples that illustrate those processes, studying some segments of science-fiction works, emphasizing scientific objects which are restored on fiction. Such analysis indicates that those objects are also submitted to defamiliarization, which takes place in a slightly different way from quotidian objects. Besides, some peculiarities of the chosen literary genre indicate that defamiliarization may occur in a particular, intensified way, in science-fiction reading.